Raman Spectroscopy 2018
DOI: 10.5772/intechopen.74065
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy Characterization of Pristine and Functionalized Carbon Nanotubes and Graphene

Abstract: Carbon nanotubes (CNTs) and graphene are at the center of a significant research effort due to their unique physical and chemical properties, which promise high technological impact. For the future development of all the foreseen applications, it is of particular interest the study of binding interactions between carbon nanostructures and functional groups. An appropriate method is the surface-enhanced Raman spectroscopy (SERS), which provides a large amplification of Raman signals when the probed molecule is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…This is generally analyzed in terms of the ratio of the I D /I G phonon peaks originating from first order spectrum [ 21 ]. However, although this analysis is well established for graphite, graphene, double and single walled nanotubes, the Raman spectrum of the MWNTs is characteristically different and more closely resembles the spectra of chars and carbon blacks [ 9 , 22 ], thus an intense D band peak is always observed, even in unfunctionalized (pristine samples). As a result of this, the conventional I D /I G ratio comparison is not as effective in giving an accurate quantitative idea of the level of disorder [ 9 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is generally analyzed in terms of the ratio of the I D /I G phonon peaks originating from first order spectrum [ 21 ]. However, although this analysis is well established for graphite, graphene, double and single walled nanotubes, the Raman spectrum of the MWNTs is characteristically different and more closely resembles the spectra of chars and carbon blacks [ 9 , 22 ], thus an intense D band peak is always observed, even in unfunctionalized (pristine samples). As a result of this, the conventional I D /I G ratio comparison is not as effective in giving an accurate quantitative idea of the level of disorder [ 9 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, although this analysis is well established for graphite, graphene, double and single walled nanotubes, the Raman spectrum of the MWNTs is characteristically different and more closely resembles the spectra of chars and carbon blacks [ 9 , 22 ], thus an intense D band peak is always observed, even in unfunctionalized (pristine samples). As a result of this, the conventional I D /I G ratio comparison is not as effective in giving an accurate quantitative idea of the level of disorder [ 9 , 22 ]. In fact, it has been shown that upon functionalization, the I D /I G ratio does not necessarily change significantly [ 9 ] and thus it is important to investigate alternative mechanisms for determining variations in functionalization and disorder.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RT Raman spectroscopy (l E ¼ 632 nm laser) further explored to characterize the ssDNA : MWNT hybridizations and the interactions with Hg 2 + ion as illustrated in Figure 4. In general, pristine graphite shows two distinct Raman features mainly [44], the G band due to strong CÀ C in-plane vibration appears around 1500 ~1600 cm À 1 (owing to E 1 2g symmetry), and the D band appears around 1300 ~1400 cm À 1 for out of plane breathing vibrational mode (A 1g symmetry) owing to the induced defects or damages to the hexagonal sp 2 networks [44]. Herein, for pristine MWNTs, the G and D bands observed at around 1568.3 cm À 1 and 1327.1 cm À 1 respectively (see Figure 4 hexagonal sp 2 network exploiting additional energy [45].…”
Section: Analysis and Discussionmentioning
confidence: 99%